Determining the effectiveness of sunscreens. (2nd July 2016) - Kennon, James Tillman; Fong, Bryant; Grippo, Anne
ABSTRACT: Sunscreens have different levels of protection, measured most commonly with the sun protection factor (SPF). Students initially believed higher SPF factors mean greater sun protection and learned through this activity that higher SPF does not mean greater protection. Students analyzed the amount of ultraviolet radiation (UVR) protection and composition of different sunscreens, first by UVR sensors in an outdoor activity and then by thin layer chromatography. These activities demonstrated that even some sunscreens provide protection from harmful UVR, and that different sunscreens, despite varying SPF factors and brand names, have similar composition. Students can apply their knowledge outside the classroom on outdoor safety and solar protection.